Implementasi Pendidikan Karakter Berbasis Kearifan Lokal dalam Membentuk Generasi Berintegritas - Moh Mundzir (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
Local wisdom-based character education has a strategic role in forming a generation with integrity, strong personality, and high moral awareness. This study aims to analyze the implementation of local wisdom-based character education in learning and identify effective strategies and obstacles faced in its implementation. Using a qualitative approach, data were collected through interviews, observations, and documentation studies. The results of the study indicate that the integration of local wisdom values ​​in education can increase cultural awareness, strengthen national identity, and form positive characters in students. However, the implementation of local wisdom-based character education still faces challenges, such as lack of understanding of educators, minimal policy support, the influence of globalization, and limited resources. Therefore, synergy is needed between schools, families, communities, and the government so that local wisdom-based character education can run effectively and sustainably.